Third World economic handbook - Sinclair, Stuart W. (London : Euromonitor Publications, 1982)
This book presents an overview of the state of the third world at the start of the 1980's, principally with the business reader in mind.
aia 07/05/2018
Loans
Keywords: Developing countries -- Economic conditions; Developing countries